Salivary testosterone and cortisol responses to seven weeks of practical blood flow restriction training in collegiate American football players - Luebbers, Paul E.; Kriley, Luke M.; Eserhaut, Drake A.; Andre, Matthew J.; Butler, Michael S.; Fry, Andrew C. (Frontiers in Physiology, 2025)
PurposeThe purpose of this study was to examine the effects of a 7-week supplemental BFR training intervention on both acute and chronic alterations in salivary testosterone (sTes) and cortisol (sCort) in collegiate American football players.Methods58 males were divided into 4 groups: 3 completed an upper- and lower-body split resistance training routine (H, H/S, H/S/R; H = Heavy, S = Supplemental, R = BFR), with H/S/R performing end-of-session practical BFR training, and H/S serving as the volume-matched non-BFR group. The final group (M/S/R) completed modified resistance training programming with the same practical BFR protocol as H/S/R. Athletes were further split into AM and PM training groups based upon their pre-determined training schedules, in cooperation with University strength and conditioning staff. Practical BFR consisted of end-of-session barbell bench press and back squat using 20% 1 repetition maximum (1RM) for 30-20-20-20 repetitions across 4 sets, with 45-seconds rest. Saliva samples were taken pre- and post- the first lower-body training sessions in week 1 and week 7 (i.e., test 1 and test 2) of the program, yielding four total. sTes and sCort were analyzed using 4-way (4 × 2 × 2 × 2) mixed model ANOVA’s.ResultsHormonal variables all exhibited main effects for time-of-day (p < 0.001). A significant group × time interaction effect (F3,50 = 3.246, p < 0.05) indicated increases in sTes post-training cycle for the H/S/R group only. Further, PM post-exercise sCort decreased from test 1 to test 2 (nmol·L−1: 95% CI: PM test 1 post-exercise = 10.7–17.1, PM test 2 post-exercise = 5.0–8.9). For the testosterone-to-cortisol ratio (T/C), AM pre-exercise was lower than PM (p < 0.05), with no change in post-exercise T/C for both AM and PM conditions when collapsed across testing times.DiscussionOverall, these findings suggest an ecologically valid method of BFR implementation is capable of inducing heightened concentrations of sTes in well-resistance trained American football athletes, providing additional insight on possible physiological mechanisms underpinning BFR’s ability to elicit beneficial muscle hypertrophy and maximal strength adaptations when performed during regimented training programs. Additionally, notable rises in T/C, and a null sCort response post-exercise were observed post-program for all groups, possibly indicative of positive physiological adaptation.